Enterprise Internationalization, Trademark Internationalization and Enterprise Value (Asian Journal of Social Science Studies, 2022)
Trademark internationalization is an important part of enterprise internationalization, and the degree of enterprise internationalization will inevitably affect the level of trademark internationalization. The practice shows that the degree of enterprise internationalization has different effects on the level of trademark internationalization and enterprise value. This article takes the Shanghai and Shenzhen A-share listed enterprises in western China from 2010 to 2019 as the research object, discusses and empirically tests the impact of trademark internationalization on enterprise value, and analyzes the moderating effect of the degree of enterprise internationalization on the relationship between the two. The study found that the level of trademark internationalization has a positive impact on enterprise value, but the degree of enterprise internationalization will have a negative impact on the relationship between the level of trademark internationalization and enterprise value. Compared with non-high-tech enterprises, the degree of internationalization of high-tech enterprises has a more significant negative regulatory effect on the level of trademark internationalization and enterprise value.